Knowledge and practice of breast self-examination among female patients attending general outpatients in BPKIHS - Giri, Rajani; Poudel, Masum (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is the most common and remains a major health problem all over the world, affecting both developing and developed countries. The strategy to detect early breast cancer is important which includes breast self-examination (BSE), clinical breast examination, and mammography. The studies have found that women who reported that they had been BSE performers had their breast cancer detected at a smaller size and earlier clinicopathological stage. There is a paucity of data on the knowledge and practice of BSE in Nepal among the female population of eastern Nepal. Therefore, this study is conducted to know the knowledge and practice of BSE among the female population attending the general outpatient department. Methods: A cross-sectional study was conducted over one and half years among 262 females attending general outpatients, using a semi-structured questionnaire. Results: The majority of the participants (29.4%) were in 3rd decade of life followed by 2nd decade (26%). Forty-one (41%) of the respondents had ever heard of BSE and the main source of information was social media (51%). Only 14.5% had adequate knowledge of BSE. Out of all, only 10.7 % were practicing BSE and the frequency of practice among them was rarely (53.5%). Seventy-two (72%) responded that they don’t know how to perform when asked why they did not perform BSE. Conclusions: This study revealed that most of the participants had low knowledge and practice of BSE. Therefore, developing a health education program to raise awareness about BSE is important.